Self-Study in Emotion Work: Organizing Chaos by Negotiating Private and Public Grief. Issue 2 (3rd May 2016) - Farnsworth, Megan
Abstract: In order to improve her practice, a teacher educator explored emotions as catalysts for teaching and learning by asking the research question, "How can I support preservice teachers' emotional intelligence (EI), as well as my own, as we negotiate the impact of strong emotions in the pedagogical environment?" Three levels of reflection (emotional, cognitive, and critical) provided a conceptual framework for organizing emotions during school violence and chaos. The year-long self-study of a small symmetrical peer-group structure provided a safe place for preservice teachers to engage in honest dialogue that allowed them to navigate professional norms. Participant frameworks and discourse analyses of transcripts revealed ways participants discursively managed (suppressed and expressed) their emotions according to the normative beliefs and expectations held about the teaching profession. Participants made connections to each other, which expanded their EI; however they also experienced disconnection from their missions (personal), due to their assessment of the teaching profession (public) as intolerant of authentic emotional display. Through self-study practices, the teacher educator claimed authority over her experiences by leveraging private emotions to call for public action, one critical step in communal healing and transformation of teaching and learning practices.